Տնտեսական ապակենտրոնացման արդյունավետությունը՝ վարչատարածքային բարեփոխումների համատեքստում - Թաթոսյան, Քրիստինե
Процесс укрупнения общин Сюникского марза практически завершен, что позволяет изучить эффективность применения децентрализации с точки зрения местного экономического развития. Актуальность темы обусловлена необходимостью оценки эффективности системы децентрализации в результате укрупнения общины, которая в нашем исследовании рассматривается в контексте местного экономического развития. The enlargement process of communities of Syunik region is almost complete, which allows studying the effectiveness of decentralization in terms of local economic development. The aim of the research is to assess the level of effectiveness of economic decentralization in Syunik region in the context of amalgamating the communities. The urgency of the topic is due to the need to assess the effectiveness of the decentralization system as a result of community enlargement, which is viewed in the context of local economic development. The enterprise operating in an arbitrary community, which uses the resources of the community during its economic activity, is expected to transmit a part of its generated funds to the community budget, so that the community authorities have a direct interest in promoting further business development.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ